(untitled) (Bangladesh Journal of Medical Science, 2021)
Objectives: The purpose of the literature review was to appraise the evidence that an early physiotherapy intervention helps to prevent the surgery in selective musculoskeletal disorders. A search of Google Scholar, Web of Science, Scopus, and PubMed was carried out utilizing the terms (“physiotherapy”, “surgery” OR “exercise, surgery” OR “rehabilitation”, “surgery”). Methods: The article titles and abstracts were screened for eligibility and included in the review. The recent literature evidently emphasized that physiotherapy has opted in selective musculoskeletal problems to avoid and delay surgeries. Results: Regardless of recommended conservative treatment option and effectiveness of physiotherapy, a massive gap can be observed between its evidence and practice. Conversely, overuse of diagnostic imaging, surgeries, and medications is present in clinical practice. In most of the clinical problems the long-term outcomes were reported the same with surgical and physiotherapy intervention. Likewise, patients can also get the advantage of better clinical outcome and cost-effectiveness with physiotherapy as compared to surgical intervention. Conclusion: The cost-effectiveness is an important factor in low-income countries where economic aspects of health care are highly considered. These advantages of physiotherapy should be considered by the clinicians, policymakers, patients, and included in the clinical guidelines. Bangladesh Journal of Medical Science Vol.20(2) 2021 p.409-413